The site of a missense mutation in the extracellular Ig or FN domains of L1CAM influences infant mortality and the severity of X linked hydrocephalus. Issue 11 (November 1998) - Michaelis, R C; Du, Y Z; Schwartz, C E
Abstract : The L1 cell adhesion molecule (L1CAM) plays an important role in axon growth, fasciculation, and neural migration. Mutations in the L1CAM gene produce a phenotype characterised by X linked hydrocephalus, mental retardation, spastic paraplegia, adducted thumbs, and agenesis of the corpus callosum. We have conducted a detailed analysis of the phenotypic effects of missense mutations in the extracellular portion of L1CAM, following a study that differentiated between "key" amino acid residues critical for maintaining the conformation of the extracellular immunoglobulin type C-like (Ig) or fibronectin type III-like (FN) domains and surface residues of less certain significance. We have analysed the data from 71 published cases and seven patients whose mutations were detected in our laboratory to determine if the site of a missense mutation in the Ig or FN domains correlated with the severity of hydrocephalus, presence of adducted thumbs, or survival past infancy. Mutations affecting the key residues in either type of domain were more likely to produce a phenotype with severe hydrocephalus, adducted thumbs, and lifespan less than one year than were mutations affecting surface residues. In addition, mutations affecting the FN domains were more likely than those affecting Ig domains to produce a phenotype with severe hydrocephalus, with less certain effects on adducted thumbs and lifespan. Mutations in key residues of the FN domains were particularly deleterious to infant survival. These data provide information that may be useful in predicting some aspects of the phenotypic effects of certain L1CAM mutations.